Applicability of Sharpe’s Single Index Model in Indian Security Model - Mehta, Sushil Kumar; Turan, M. S. (Indian Journal of Finance, 2008)
The paper attempts to analyse the applicability of Sharpe’s Single Index Model in Indian Security Market based on the ex-ante performance of Portfolios constructed using the model. Weekly data on market prices of 50 shares, listed on Bombay Stock Exchange, and 30 stock BSE Sensitive Index was collected for a period of 7 years ranging from April 1995 to March 2002. 23 portfolios were constructed using the model. These portfolios were tested for their performance during one year immediately following their construction using well established risk adjusted portfolio evaluation measures of Sharpe, Treynor, Jensen and Fama. The results of the study indicated that in case of 56.52 to 65.22 per cent of the portfolios, the performance appears to be superior to the market. However, it is not significantly superior at 10 per cent level of significance.